Human development in South Asia 1998 - Mahbub ul Haq; Chandra, Ashoka; Institute for Human Development (New Delhi, India); Institute of Applied Manpower Research (India); Friedrich-Ebert-Stiftung. (Dhaka : The University press, 1998)
Contributed articles presented at a conference.
Includes bibliographical references and index.
Keywords: Labor market -- India; Industrial relations -- India; Manpower policy -- India; Poor -- India